2012
DOI: 10.1111/j.1346-8138.2011.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides in the pathogenesis of psoriasis

Abstract: One characteristic abnormality of lesional skin in psoriasis is the excessive production of antimicrobial peptides and proteins (AMPs). AMPs typically are small (12-50 amino acids), have positive charge and amphipathic structure, and are found in all living organisms including mammals, insects, plants and invertebrates. These peptides are best known for their integral role in killing pathogenic microorganisms; however, in vertebrates, they are also capable of modifying host inflammatory responses by a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
189
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(192 citation statements)
references
References 78 publications
1
189
0
2
Order By: Relevance
“…In agreement with this, CXCR2 density is elevated on neutrophils from psoriatic individuals compared with those from healthy volunteers (35), along with increased IL-8 and CXCL1 levels in psoriatic epidermis (29). Furthermore, cathelicidin antimicrobial peptide (also known as LL-37), another potential ligand for CXCR2 (36), is overexpressed in human psoriatic keratinocytes and has been suggested to play a role in the pathogenesis of inflammatory skin diseases including psoriasis (37,38). Much to our interest, cathelicidin triggers LTB 4 synthesis from human neutrophils (39), as well as CXCL1 and CXCL2, as shown in Fig.…”
Section: Discussionsupporting
confidence: 51%
“…In agreement with this, CXCR2 density is elevated on neutrophils from psoriatic individuals compared with those from healthy volunteers (35), along with increased IL-8 and CXCL1 levels in psoriatic epidermis (29). Furthermore, cathelicidin antimicrobial peptide (also known as LL-37), another potential ligand for CXCR2 (36), is overexpressed in human psoriatic keratinocytes and has been suggested to play a role in the pathogenesis of inflammatory skin diseases including psoriasis (37,38). Much to our interest, cathelicidin triggers LTB 4 synthesis from human neutrophils (39), as well as CXCL1 and CXCL2, as shown in Fig.…”
Section: Discussionsupporting
confidence: 51%
“…Antimicrobial peptides (AMPs) constitute one such class of potential anti-infective drugs, and are currently receiving much attention in both academic research and drug development (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, anti-TNF is a mainstay of therapy for psoriasis, and anti-IL-17A therapy was recently approved as a first-line systemic treatment (10,11). While the involvement of peptide-reactive T cells has been well defined (12)(13)(14)(15), the role of lipid-reactive T cells in psoriasis remains largely unknown. Since psoriasis and cardiovascular disease are correlated with hyperlipidemia and recent studies have identified CD1-restricted self-lipid-reactive T cells in the blood or skin of humans (16)(17)(18)(19), we developed a new mouse model for the study of human CD1-restricted T cell responses to self-lipids in vivo.…”
Section: Introductionmentioning
confidence: 99%